(untitled) (Research, Society and Development, 2020)
The aim of this in vitro study was to evaluate the effectiveness of dental bleaching run concurrent with orthodontic treatment and its effect on the bond strength of brackets after bleaching. Sixty bovine teeth were divided into three groups (n = 20), one group was subjected only to the bonding of brackets (G1) and another in the bonding of brackets and dental bleaching (G2) and G3, subject only to dental bleaching. Ran up the collage of brackets in the samples of G1 and G2. After gluing, the samples of G2 and G3 were subjected to bleaching with hydrogen peroxide 35%. After 24 hours, we carried out the analysis of tensile strength by shear testing the samples of G1 and G2 and subsequent analysis of the efficiency of clearing, in G2 and G3, with the help of the spectrophotometer manual Easyshade® by the CIE L * a * b * color parameters. The data were tested using” t-student "no-test at 5% significance for the analysis of tensile strength and the Mann-Whitney 5% for comparisons between groups in analyzing the efficiency of bleaching treatment. G1 had average strength of tensile strength of 13.34 MPa and 12.56 MPa in group G2, no statistically significant difference (p = 0.425). Within each single parameter L * a * b * and ΔE value, there was no statistically significant differences between G2 and G3 (p> 0.05). The bleaching did not affect the bond strength of brackets and was able to promote dental bleaching in the region under the orthodontic bracket.